Animation lab for kids : fun projects for visual storytelling and making art move - Bellmont, Laura; Brink, Emily (Quarry Books, 2016)
"In Animation Lab for Kids, artists, teachers, and authors Laura Bellmont and Emily Brink present exciting, fun, hands-on projects that teach kids a range of animation techniques."--